Differential Changes in Akt and AMPK Phosphorylation Regulating mTOR Activity in the Placentas of Pregnancies Complicated by Fetal Growth Restriction and Gestational Diabetes Mellitus With Large-For-Gestational Age Infants - Hung, Tai-Ho; Wu, Chung-Pu; Chen, Szu-Fu (Frontiers in Medicine, 2021)
Background: Dysregulation of placental mechanistic target of rapamycin (mTOR) activity has been implicated in the pathophysiology of pregnancies complicated by idiopathic fetal growth restriction (FGR) and gestational diabetes mellitus (GDM) with large-for-gestational-age (LGA) infants. However, the underlying mechanisms remain unclear. Methods: We obtained placentas from women with normal pregnancies (n=11) and pregnancies complicated by FGR (n=12) or GDM with LGA infants (n=12) to compare the levels of total and phosphorylated forms of Akt, AMPK, TSC2, and mTOR among the three groups and used primary cytotrophoblast cells isolated from 30 normal term placentas to study the effects of oxygen–glucose deprivation (OGD) and increasing glucose concentrations on the changes of these factors in vitro. Results: Placentas from FGR pregnancies had lower phosphorylated Akt (p-Akt) levels (P <0.05), higher p-AMPKlevels (P <0.01), and lower mTOR phosphorylation (P <0.05) compared to that of normal pregnant women. Conversely, women with GDM and LGA infants had higher p-Akt (P <0.001), lower p-AMPK(P <0.05), and higher p-mTOR levels (P <0.05) in the placentas than normal pregnant women. Furthermore, primary cytotrophoblast cells subjected to OGD had lower p-Akt and p-mTOR (both P <0.05) and higher p-AMPK levels (P <0.05) than those cultured under standard conditions, but increasing glucose concentrations had opposite effects on the respective levels. Administering compound C, an AMPK inhibitor, did not significantly affect Akt phosphorylation but partially reversed mTOR phosphorylation. Administering LY294002, an Akt inhibitor, decreased p-mTOR levels, but did not change the levels of total and phosphorylated AMPK. Conclusion: These results suggest that Akt and AMPK are involved in the regulation of trophoblast mTOR activity in the placentas of pregnancies complicated by FGR and GDM with LGA infants.